Teachings of Violence in Education: Review of War Material on Islamic Cultural History Subjects at the Elementary Level - Muhamad Tisna Nugraha (Postgraduate Program Magister Pendidikan Agama Islam, 2019)
Education is one of the instruments considered the most effective in preparing students before entering real life. Education is also considered as a vehicle that can solve social problems, instilling religious and humanitarian values. For this reason, in school, there is no place for material that presents violent content and or material that contains radical notions. However, the existence of several articles about warfare in the subjects of the History of Islamic Culture (SKI), causing anxiety that gave birth to the idea to replace the material content, because it was feared could foster fanaticism and religious intolerance. This paper departs from library research (library research) using a qualitative approach. Library research referred to in this paper is a study that makes library materials as the primary source of research. Also, in this paper observation and documentation techniques are also used which are processed using qualitative analysis to find out the teachings of violence in education on war material in the subjects of the history of Islamic culture at the elementary level. Based on the results of the study it can be seen that no teachings or content contain violence, radicalism, fanaticism and religious intolerance in the material of warfare in the subject of Islamic Cultural History at the primary level. The proportion of SKI subjects turned out to only have 2 hours (JP) in 1 week or equal to 4.65% of the total 43 JP learning loads in the curriculum structure of Madrasah Ibtidaiyah (MI) in grades 4, 5 and 6. Whereas in grade 3, the proportion of SKI subjects is slightly higher by 0.35% or reaches 5% of the total 40 JP study load in one week in the MI curriculum structure. Pendidikan merupakan salah satu instrumen yang dianggap paling ampuh dalam mempersiapkan peserta didik sebelum memasuki kehidupan nyata. Pendidikan juga dianggap sebagai wahana yang dapat memecahkan masalah-masalah sosial, menanamkan nilai-nilai keberagamaan dan kemanusiaan. Untuk itu, dalam pendidikan tidak ada tempat bagi materi-materi yang menyajikan konten-konten kekerasan dan atau materi yang berisi paham-paham radikalisme. Namun adanya sejumlah materi tentang peperangan di mata pelajaran Sejarah kebudayaan Islam (SKI), menimbulkan kegelisahan yang melahirkan gagasan untuk mengganti muatan materi tersebut, karena dikhawatirkan dapat menumbuhkan sikap fanatisme dan intoleransi beragama. Tulisan ini berangkat dari studi kepustakaan (library research) dengan menggunakan metode pendekatan kualitatif. Penelitian pustaka yang dimaksud dalam tulisan ini adalah suatu penelitian yang menjadikan bahan pustaka sebagai sumber utama penelitianya. Selain itu, dalam tulisan ini juga digunakan teknik observasi dan dokumentasi yang diolah dengan menggunakan analisa kualitatif dengan tujuan untuk mengetahuai ajaran kekerasan dalam pendidikan pada materi peperangan di mata pelajaran sejarah kebudayaan Islam tingkat dasar. Berdasarkan hasil penelitian dapat diketahui bahwa tidak ada ajaran atau muatan yang berisi kekerasan, radikalisme, fanatisme dan intoleransi beragama pada materi peperangan di mata pelajaran Sejarah Kebudayaan Islam tingkat dasar. Bahkan, proporsi mata pelajaran SKI ternyata hanya memilki bobot 2 jam pelajaran (JP) dalam 1 minggu atau setara dengan 4,65% dari total 43 JP beban belajar dalam struktur kurikulum Madrasah Ibtidaiyah (MI) di kelas 4, 5 dan 6. Sedangkan di kelas 3, proporsi mata pelajaran SKI sedikit lebih tinggi 0,35% atau mencapai angka 5% dari total 40 JP beban belajar dalam satu minggu di struktur kurikulum MI.